A comparative study on macroscopic and nanoscale polarization mapping on large area PLD grown PZT thin films. Issue 8 (1st June 2018) - Rath, Martando; Varadarajan, E.; Natarajan, V.; Ramachandra Rao, M.S.
Abstract: By optimizing laser raster scanning conditions and controlling PbO evaporation, we have grown high quality large area PbZr.52 Ti.48 O3 (PZT) thin films using custom-built off-axis pulsed laser deposition (PLD) technique. The realization of high quality PZT thin films over a large area with uniform polarization is a challenging task due to the formation of non-ferroelectric or pyrochlore like PbTi3 O7 phases at the processing temperature ( > 600 ° C ). Our results show the polycrystalline nature of the sample with a uniform chemical surface composition. The macroscopic level of polarization mapping shows excellent saturated P-E loops with a narrow variation (6%) of the remnant polarization (2P r ) across the large area thin films. A comparative study of macroscopic and nanoscale level of mapping of polarization switching are performed, to demonstrate the existence of stoichiometry ferroelectric PZT thin films over a large area. The achievement of high quality large area PZT thin films with uniform polarization might be used for under-water SONAR devices and in power harvesting.